2018
DOI: 10.48550/arxiv.1810.10159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurements of Dielectron Production in Au$+$Au Collisions at $\sqrt{s_{NN}}$= 27, 39, and 62.4 GeV from the STAR Experiment

Abstract: We report systematic measurements of dielectron (e ± e ± ) invariant-mass Mee spectra at midrapidity in Au+Au collisions at √ sNN = 27, 39, and 62.4 GeV taken with the STAR detector at the Relativistic Heavy Ion Collider. For all energies studied, a significant excess yield of dielectrons is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…At low lepton pair transverse momentum(q ⊥ ), the dominant production mechanism is the photon-photon fusion process(γγ → l + l − ) which is greatly enhanced due to the large flux of quasi-real photons coherently generated by a fast moving nucleus. The measurements carried out at SPS, RHIC and LHC [1][2][3][4][5][6][7] have clearly demonstrated that dilepton production is indeed peaked at very low transverse momentum. The comprehensive understanding of such process is not only important for accurate background estimates in heavy ion collisions, but also interesting from a pure theoretical point of view.…”
Section: Introductionmentioning
confidence: 98%
“…At low lepton pair transverse momentum(q ⊥ ), the dominant production mechanism is the photon-photon fusion process(γγ → l + l − ) which is greatly enhanced due to the large flux of quasi-real photons coherently generated by a fast moving nucleus. The measurements carried out at SPS, RHIC and LHC [1][2][3][4][5][6][7] have clearly demonstrated that dilepton production is indeed peaked at very low transverse momentum. The comprehensive understanding of such process is not only important for accurate background estimates in heavy ion collisions, but also interesting from a pure theoretical point of view.…”
Section: Introductionmentioning
confidence: 98%
“…A systematic beam-energy scan study (BES) by the STAR collaboration of the production of dielectrons in the lowmass range [283] has recently been augmented by two high-statistics data samples at √ s NN = 27 GeV and 54.4 GeV [281,284]. As shown in the left panel of Fig.…”
Section: Recent Experimental Resultsmentioning
confidence: 99%
“…8.5 shows a compilation of experimental results on the integrated LMR dilepton excess radiation for different beam energies. These results were obtained by the HADES collaboration [242], the NA60 collaboration [14,15], and the STAR collaboration [244]. All shown data points are acceptance-corrected and represent the excess radiation as obtained by subtracting cocktail contributions excluding the ρ-meson (since its contributions are expected to be strongly modified by the medium) from the dielectron yields.…”
Section: Dileptons As a Thermometer And Chronometermentioning
confidence: 98%
See 1 more Smart Citation
“…Here, we will concentrate specifically on the dilepton emission. Recently, several measurements of the dilepton production were reported by both RHIC and LHC [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%